Facile electrochemical approach for the production of graphite oxide with tunable chemistry. (February 2017) - Tian, Zhiming; Yu, Pei; Lowe, Sean E.; Pandolfo, Anthony G.; Gengenbach, Thomas R.; Nairn, Kate M.; Song, Jingchao; Wang, Xin; Zhong, Yu Lin; Li, Dan
Abstract: Reproducible and in-depth studies of the electrochemical graphite intercalation and oxidation processes were carried out with the use of an electrochemical Tee-cell setup. The electrochemical method allowed simpler and greater controllability over the level of oxidation/functionalization, relative to the commonly employed chemical oxidation approach (e.g. the modified Hummers method). Extensive characterization was carried out to understand the properties of the electrochemically-derived graphite oxide (EGrO), and it was found that the abundance of each functionality was highly dependent on the electrochemical reaction time or the concentration of the electrolyte (perchloric acid) employed. Notably, the amount of oxygen functional groups on EGrO could be as high as 30 wt%, but the degree of oxidation did not proceed beyond the generation of carbonyl species. The controllable oxidation level of the EGrO makes it an attractive precursor for many applications, such as electronics and nanocomposites. Graphical abstract: